A blockchain course for accounting and other business students. (September 2021) - Stern, Myles; Reinstein, Alan
Highlights: How to add blockchain as a separate course or an addition to an existing course. Course syllabus, suggested readings, group and individual assignments. Blockchain's novelty and complexity (Iansiti and Lakhan, 2017). Build student knowledge from basic blockchain concepts to business applications. Abstract: We describe how accounting and other business professors can add blockchain as a separate course or an addition to an existing course. Based upon a popular, online course at Wayne State University (WSU), we provide examples of a course syllabus, suggested readings, group and individual assignments materials, and student comments. This course addresses two key features that Iansiti & Lakhan (2017) identified about blockchain: novelty and complexity. Given blockchain's complexity and growing prominence in business, this course develops students' knowledge, starting with understanding blockchain's basic concepts and advancing to focus on business applications.